Interplay between geopolymer formulation, microstructure, and strontium sorption properties - A. Varon; A. Gossard; Y. Coppel; Y. Barré; A. Poulesquen (Cleaner Materials, 2025)
This article focused on developing chemically stable, high-performance adsorbents for selective Sr2+ removal from nuclear wastewater, enabling safer long-term storage and disposal. Geopolymers, due to the negative charge of aluminum acting as a sorption exchange site (AlIV), promote ion exchange, thereby exhibiting favourable adsorption kinetics and exchange capacities. A novel approach is developed to comprehensively characterize geopolymers and establish structure-sorption property relationships. This study examines how key synthesis factors, specifically the Si/Al and H2O/M2O molar ratios, influence structural properties, characterized by nitrogen adsorption–desorption and 27Al and 29Si Nuclear Magnetic Resonance (NMR). These techniques probe material structural properties and AlIV concentration, enabling assessment of their impact on strontium and calcium sorption behaviour. Increasing the Si/Al ratio enhances porosity but reduces AlIV concentration, thereby diminishing sorption capacity. This decline is attributed to greater distances between AlIV units and a structural shift toward a more silicon-dominated network. A 2D surface state model based on the Q4(mAl) silicon centers from the 29Si NMR was developed to correlate it to the sorption properties of the geopolymer. Selectivity toward the strontium is observed for Si/Al = 1.52, highlining the impact of the porous structure and silicon environment, with favourable distance between AlIV sites for strontium sorption over calcium. Similarly, increasing the H2O/K2O ratio improves sorption properties. However, once a specific ratio is reached (H2O/K2O = 12), microstructure no longer influence sorption properties. Silicon environment differ across compositions, influencing selectivity factor H2O/K2O = 12, exhibiting the highest one, indicating a more suitable sorption environment.